2017
DOI: 10.1186/s12944-017-0565-8
|View full text |Cite
|
Sign up to set email alerts
|

Lipase and biosurfactant from Ochrobactrum intermedium strain MZV101 isolated by washing powder for detergent application

Abstract: BackgroundAlkaline thermostable lipase and biosurfactant producing bacteria are very interested at detergent applications, not only because of their eco-friendly characterize, but alsoproduction lipase and biosurfactant by using cheap materials. Ochrobactrum intermedium strain MZV101 was isolated as washing powder resistant, alkaline thermostable lipase and biosurfactant producing bacterium in order to use at detergent applications.Methods O. intermedium strain MZV101 produces was lipase and biosurfactant in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 81 publications
1
24
0
Order By: Relevance
“…(Table 1). Lipase production by S. hominis and by Ochrobactrum intermedium has been reported (Zarinviarsagh et al, 2017;Behera et al, 2019), which validates our results of lipase production. Although isolates of the genus Klebsiella have been shown to produce lipase in bioprospection studies (Mazzucotellii et al, 2013), none has been studied in detail, and the production of lipase by the K. variicola species is a new finding.…”
Section: Discussionsupporting
confidence: 90%
“…(Table 1). Lipase production by S. hominis and by Ochrobactrum intermedium has been reported (Zarinviarsagh et al, 2017;Behera et al, 2019), which validates our results of lipase production. Although isolates of the genus Klebsiella have been shown to produce lipase in bioprospection studies (Mazzucotellii et al, 2013), none has been studied in detail, and the production of lipase by the K. variicola species is a new finding.…”
Section: Discussionsupporting
confidence: 90%
“…One of the earliest studies supporting this hypothesis showed that cell formation can be induced by corticosteroids, granulocyte-macrophage (GM)-CSF, or IL-10, and a key feature is the cells that respond to IL-17 become resistant to apoptosis ( Table 1). 70…”
Section: Macrophage Phenotypesmentioning
confidence: 99%
“…Ochrobactrum spp. are metabolically versatile and exhibit some unique features, e.g., O. intermedium MZV101 is able to produce lipase and biosurfactants at pH 10 and temperature of 60 °C [ 21 ]. What is more, Ochrobactrum spp.…”
Section: Introductionmentioning
confidence: 99%